2017
DOI: 10.1016/j.bpj.2016.12.035
|View full text |Cite
|
Sign up to set email alerts
|

Two Distinct Actin Networks Mediate Traction Oscillations to Confer Focal Adhesion Mechanosensing

Abstract: Focal adhesions (FAs) are integrin-based transmembrane assemblies that connect a cell to its extracellular matrix (ECM). They are mechanosensors through which cells exert actin cytoskeleton-mediated traction forces to sense the ECM stiffness. Interestingly, FAs themselves are dynamic structures that adapt their growth in response to mechanical force. It is unclear how the cell manages the plasticity of the FA structure and the associated traction force to accurately sense ECM stiffness. Strikingly, FA traction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 66 publications
3
50
0
Order By: Relevance
“…Previous studies demonstrated that cells respond to the mechanical demands of the local microenvironment by dynamically altering their actin cytoskeleton at focal adhesions (FAs; Choquet et al, 1997;Butcher et al, 2009). In agreement with these findings, mathematical and experimental modeling suggested that the acto-myosin cytoskeleton at FAs mediates an oscillating traction force required for mechanically directed motility, the directional movement toward a mechanical stimulus (Plotnikov et al, 2012;Wu et al, 2017). However, the mechanisms that regulate these FA cytoskeletal dynamics and the distinctive role they play in mechanosensing, mechanically directed motility, and durotaxis have yet to be elucidated.…”
Section: Introductionmentioning
confidence: 61%
“…Previous studies demonstrated that cells respond to the mechanical demands of the local microenvironment by dynamically altering their actin cytoskeleton at focal adhesions (FAs; Choquet et al, 1997;Butcher et al, 2009). In agreement with these findings, mathematical and experimental modeling suggested that the acto-myosin cytoskeleton at FAs mediates an oscillating traction force required for mechanically directed motility, the directional movement toward a mechanical stimulus (Plotnikov et al, 2012;Wu et al, 2017). However, the mechanisms that regulate these FA cytoskeletal dynamics and the distinctive role they play in mechanosensing, mechanically directed motility, and durotaxis have yet to be elucidated.…”
Section: Introductionmentioning
confidence: 61%
“…However, focal adhesions do not display this behaviour, but rather increase their traction force monotonically as the stiffness increases (Ghibaudo et al, 2008). This finding suggests that there is a mechanism that reinforces the clutch so that it can operate at higher traction force, which turns out to require both talin and vinculin (Elosegui-Artola et al, 2016; see also new computational model from Wu et al, 2017).…”
Section: The Talin Rod -A Mechanotransducer With Multiple Statesmentioning
confidence: 98%
“…They are believed to drive cell motion, shape changes, and extracellular matrix remodeling [1][2][3]. However, most of the traction force analysis has been performed on stationary cells, investigating forces at the level of individual focal adhesions or linking them to static cell parameters such as area and edge curvature [4][5][6][7][8][9][10]. It is not well understood how traction forces are related to shape changes and motion, e.g.…”
mentioning
confidence: 99%